2016
DOI: 10.1002/ceat.201600216
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Coupling of Methane: Opportunities for Microkinetic Model‐Assisted Process Implementations

Abstract: Oxidative coupling of methane is a low‐cost alternative for ethylene production. However, its high exothermicity, complex reaction network, and low selectivity to C2 products require more in‐depth analysis for economically viable process implementation. Microkinetic modeling enables assessment of operating conditions and catalyst properties on the overall performance via elementary gas‐phase and catalytic reactions. The know‐how to reproduce and interpret experimental kinetic data, especially the role of highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…Based on the evaluated scientific papers, seven different main subject streams have been identified: (1) modelling of the OCM process, embracing phenomenological and empirical mathematical descriptions of reactors and respective chemical kinetics [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], but also involving theoretical analyses of mechanistic models [23][24][25][26][27][28][29]; (2) economic evaluation of actual OCM commercial implementations, involving the analysis of capital and operational costs [30][31][32][33][34][35]; (3) assessment of environmental impacts, mainly involving the analysis of CO 2 emissions [31]; (4) development of new and/or improved catalysts for the production of ethylene from OCM reactions [27,; (5) development of alternative processes for CH 4 conversion into ethylene and/or other products, including, for instance, the non-oxidative coupling of methane [74][75][76]; (6) investigation of downstream purification strategies [77][78][79], concerning mainly the separation of products from the OCM reactor output stream; and finally, (7) the design, optimisation and development of OCM reactors for ethylene production, including the analysis of distinct reactor concepts (such as chemical looping…”
Section: What Are Ocm Scientific Publications and Patents About?mentioning
confidence: 99%
“…Based on the evaluated scientific papers, seven different main subject streams have been identified: (1) modelling of the OCM process, embracing phenomenological and empirical mathematical descriptions of reactors and respective chemical kinetics [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], but also involving theoretical analyses of mechanistic models [23][24][25][26][27][28][29]; (2) economic evaluation of actual OCM commercial implementations, involving the analysis of capital and operational costs [30][31][32][33][34][35]; (3) assessment of environmental impacts, mainly involving the analysis of CO 2 emissions [31]; (4) development of new and/or improved catalysts for the production of ethylene from OCM reactions [27,; (5) development of alternative processes for CH 4 conversion into ethylene and/or other products, including, for instance, the non-oxidative coupling of methane [74][75][76]; (6) investigation of downstream purification strategies [77][78][79], concerning mainly the separation of products from the OCM reactor output stream; and finally, (7) the design, optimisation and development of OCM reactors for ethylene production, including the analysis of distinct reactor concepts (such as chemical looping…”
Section: What Are Ocm Scientific Publications and Patents About?mentioning
confidence: 99%
“…In the presence of oxygen, solid oxide catalysts can form active surface oxygen species that selectively abstract one hydrogen from methane to release free methyl radicals(CH 3 ·)in the gas phase, which subsequently couples to form ethane. The reaction is followed by the dehydrogenation of ethane to form ethylene or by the irreversible formation of oxidation products (CO or CO 2 ) . Furthermore, it was reported that electrophilic lattice oxygen species and the facile filling of surface lattice oxygen vacancies by gas‐phase oxygen are key factors to design efficient catalysts for the oxidative coupling of methane .…”
Section: Co2 Oxidative Coupling Of Methanementioning
confidence: 99%
“…Methane is the most stable hydrocarbon due to its strong C‐H bond (434 kJ/mol) and thus its activation needs a high temperature. There are various techniques to convert methane to more valuable chemicals and fuels, which can be classified into three types of routes: (1) reforming to produce syngas including steam reforming (Equation ), dry reforming (Equation ), and partial oxidation (Equation ); (2) oxidative coupling (Equation and Equation ); and (3) conversion to oxygenates such as methanol (Equation ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methane as the main component of natural gas and a predominant hydrocarbon feedstock can be used to produce ethyne, chloromethane, carbon black, and so on, which becomes a relatively inexpensive and alternative energy resource to crude oil. [1][2][3][4][5][6] The abundant production and reserves of natural gas are beneficial to producing the valueadded chemicals, but also cause the problem of global warming. 5,[7][8][9][10] Therefore, the efficient conversion of methane is highly desired from aspects of the environmental protection and high-efficacy utilization of fossil fuel.…”
Section: Introductionmentioning
confidence: 99%